Teacher Teaching Creativity and Interactional Communication on Student Learning Achievement - Elysia, Eda; Sarah, May (Semantik: Journal of Social, Media, Communication, and Journalism, 2023)
This research aims to determine the influence of teacher teaching creativity and interactional communication on student learning achievement. This research uses qualitative research with a descriptive approach. The results of this research are that teachers must have learning methods in teaching science. In the communication process between teachers and students, it can be seen that this gives rise to an interactional communication model. This interactional communication model is a communication model that is often used in everyday life and can build children's creativity. Education is a very important thing for someone to gain knowledge and improve one's self-quality. With the aim of this education, it can determine whether a person is successful or not based on the results they have achieved. There are several things that influence student learning achievement, in this case teaching creativity and communication between teachers and students are factors in achieving learning achievement